Analysis and Verification of Traveling Wave Resonance Characteristics of a Spiral Bevel Gear System - Jia Yaping; Qian Lulu; Zhang Huanzhang; Lou Peng (Jixie chuandong)
A spiral bevel gear system of the aero-engine is taken as the research object. A method of gear system-level traveling wave resonance characteristics analysis of bevel gears is proposed. Based on design parameters and machining parameters, a 3D model of spiral bevel gear pairs with accurate tooth surface is established. The static mechanical analysis of the spiral bevel gear system is carried out to ensure the normal contact of the gears. The pre-stressed modal analysis is conducted to obtain the modal characteristics of the gear system. Based on the traveling wave resonance theory, the traveling wave resonance of the bevel gear system is predicted. The result is compared with the experimental data to verify the accuracy and effectiveness of the method. The results show that the theoretical analysis is in good agreement with experimental results. This study provides a valuable reference method for resonance prediction of the spiral bevel gear system.